Radiographic Soft Tissue Thickness Is Not a Risk Factor for Infection after Primary Total Ankle Arthroplasty - Albert T. Anastasio MD; Kevin Wu BS; Katherine Kutzer BS; Alexandra Krez MD; James K. DeOrio MD; Mark E. Easley MD; James A. Nunley MD; Samuel B. Adams MD (Foot & Ankle Orthopaedics, 2024)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) is a commonly performed surgical procedure to address end-stage arthritis. Previous studies have suggested that the radiographic soft tissue thickness may be a predictor of complications including periprosthetic joint infection (PJI) after orthopedic surgery. However, there has been limited studies exploring the use of radiographic soft tissue thickness in TAA. The purpose of this study was to evaluate the predictive capabilities of radiographic soft-tissue thickness for PJI following TAA. Methods: A retrospective analysis of 323 patients at a single institution who underwent primary TAA from 2003 to 2019 was conducted. Patient characteristics, including age, sex, body mass index (BMI), and comorbidities such as diabetes, smoking status, and etiology of ankle injury were recorded. Preoperative radiographic measurements, including the Tibial-Tissue and Talus-Tissue distances were recorded. Other perioperative information included prosthesis type, tourniquet time, and time to last follow-up. Logistic regression was utilized to examine the relationship between these factors and the occurrence of PJI. Results: Of the 323 patients, there were 6 patients (1.86%) who developed a PJI. The logistic regression analysis revealed that neither Tibial-Tissue (Odds Ratio: 0.975 [0.947 - 1.004]; p = 0.09) nor Talus-Tissue thickness (Odds Ratio: 0.976 [0.940 - 1.012]; p = 0.18) were significant predictors of PJI. Although not statistically significant, the infected cohort had smaller average Tibial-Tissue (2.20 vs. 2.53 cm; p=0.05) and Talus-Tissue thickness (2.19 vs. 2.44 cm; p=0.36) compared to the non-infected cohort. Conclusion: Despite an association between radiographic soft tissue thickness and infection in other orthopedic surgeries, measurements such as Tibial-Tissue length and Talus-Tissue length were not significant predictors of PJI following primary TAA. These findings underscore the necessity for additional research to identify modifiable risk factors aimed at reducing PJI rates and enhancing patient outcomes.